1998
DOI: 10.1111/j.1442-9071.1998.tb01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pterygium and pinguecula: The Blue Mountains Eye Study

Abstract: The study found significant associations between pterygium and increased pigmentation (skin and hair colour), decreased skin sun sensitivity and sun-related skin damage. The age- and sex-specific pterygium prevalence rates in the present study are simi ar to rates found in non-Aboriginals examined in the 1980 Australian Trachoma Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
131
8
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 11 publications
16
131
8
8
Order By: Relevance
“…15 In the Blue Mountain Eye Study, the prevalence was 7.3% for participants aged 49 years or older. 21 The prevalence of pterygium among 477 residents on a tropical island in Indonesia, however, was high, at 17.0%, 22 and the black population of the Barbados Eye Study was even higher, 23.4% of 2617 participants were aged 40-84 years. 23 The highest prevalence of pterygium, to our knowledge, was in subjects aged 50 years or above in a rural area of southern China, 33.01%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…15 In the Blue Mountain Eye Study, the prevalence was 7.3% for participants aged 49 years or older. 21 The prevalence of pterygium among 477 residents on a tropical island in Indonesia, however, was high, at 17.0%, 22 and the black population of the Barbados Eye Study was even higher, 23.4% of 2617 participants were aged 40-84 years. 23 The highest prevalence of pterygium, to our knowledge, was in subjects aged 50 years or above in a rural area of southern China, 33.01%.…”
Section: Discussionmentioning
confidence: 97%
“…The HES found no statistical significance in pterygia between men and women, which is consistent with some reports. 9,21,28,29 From two studies conducted in China, women were at higher risk than men. 10,20 The Blue Mountains Eye study 21 and the Tanjong Pagar survey 15 found that men were at higher risk than women; similar results were found by McCarty et al 9 and Moran and Hollows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pterygium is a worldwide ocular disease which is particularly more common in tropical and sub tropical area [20][21][22][23]. The development of a pterygium can lead to significant astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…The development of pinguecula is associated with aging. [1][2][3][4][5][6] We previously examined the incidence of conjunctivochalasis in a hospital-based population 7 and in contact lens (CL) wearers. 8 We found that the prevalence and severity of conjunctivochalasis were dependent on both the age 7 of the subjects and the duration of wearing CLs.…”
Section: Introductionmentioning
confidence: 99%